Rhetorical fallacies as persuasive strategies and their ideologies in the political speeches of prime minister Nouri Al-Maliki - Hamad, Saad Saleh (2021)
Critical discourse analysis focuses on social problems and political topics, specifically on how power relations are presented and abused in a given discourse. It aims at analyzing discourse linguistically by relating linguistic behavior to political behavior. Political discourse is deliberately constructed for political aims; it intends to impose certain beliefs and attitudes upon people. These beliefs and attitudes comprise politicians' underlying ideologies, and according to these ideologies, politicians construct their language by which they aim to persuade people and thereby exercise power and dominance over them. However, in political discourse, politicians may use faulty logic in constructing their language, In that people might easily fall for fallacies. The study aimed to (1) determine Nouri al-Maliki's rhetorical fallacies; (a) the violated rules in committing these fallacies; (b) the argument scheme that constructed such fallacies; (2) analyze the speech acts used in performing such fallacies; (3) how fallacies and their speech acts accomplish the process of persuasion; (4) determine the ideologies commonly propagated by Nouri al-Maliki through the use of fallacies. The present study adopted a qualitative research design for data collection and data analysis. The data consist of eleven political speeches of the former Prime Minister of Iraq Nouri al-Maliki. The speeches were examined using Van Eemeren et al.'s (2002) pragma-dialectical approach, Walton's (2007) commitment-based approach, and Van Dijk's (2006) socio-cognitive approach. For data analysis, a textual analysis method was used following the critical discourse analysis approach. The findings revealed that al-Maliki violated eight out of ten critical discussion rules, committing 22 out of 31 fallacies within these rules. Furthermore, al-Maliki performed such fallacies with a variety of complex speech acts, including assertives, directives, and commissives. The use of fallacies and their complex speech acts played an essential role in making al-Maliki's political speeches persuasive. Finally, al- Maliki's ideology was founded on religious sectarianism and was used to convey a variety of themes, including terrorism, sectarianism, human rights, and democracy. The current study provides several significant contributions to the body of knowledge. It is the first study that uses the Pragma-dialectical approach to analyze political discourse, as this model has only been used to analyze political debate. The study identifies two types of fallacies that have not been included in the Pragma-dialectical approach, indicating its lack of inclusiveness. As the first comprehensive study on fallacies, the current study provides a significant contribution to this field by shedding light on various types of rhetorical fallacies. It also contributes to the field of political discourse by basing the analysis on the validity of an argument and the role of speech acts, recognizing both the socio-philosophical and socio-linguistic foundations of rhetorical fallacies.